Design For Manufacturability (DFM) Of 3D Printed Parts Fabricated Using Open Source 3D Printer - Maidin, Nurul Ain; Ab Rahman, Mohd Hidayat; Ahmad, Mohd Nazri; Wahid, Mohammad Khalid; Osman, Mohd Hairizal; Jumaidin, Ridhwan; Mazlan, Siti Nur Humaira; Mohd Basri, Mohd Salahuddin (Penerbit UTHM, 2020)
Fused deposition modeling (FDM) is one of the well-known additive manufacturing (AM) techniques to fabricate the part using layer-by-layer concept. Recently, an open source 3D printer is become widely available used by 3D printer user because of its affordability and portability. In this study, the performance of an open source 3D printer was evaluated based on the dimensional accuracy of the printed parts. The test model was fabricated using two types of printer, which is low cost 3D printer, Prusa and mid-end 3D printer, Cubepro. Then, the dimension of every model structure was measured using Rexscan 3D laser scanner and was compared.